Studies on Transportation of Fish I Packaging of Frozen Fish in Insulated Containers - PERIGREEN, A. (Fishery Technology, 1968)
The paper deals with certain technological aspects of transportation of fish. Frozen fish packed in thermocole insulated plywood box (tea chests) and transported has been found to remain in good condition, for 3 to 4 days. Fish reaching the destination in a thawed state can be stored in crushed ice for a further period of 2-3 days. The effect of initial temperature of frozen fish on the storage life, the maximum storage period for different types of frozen fish packed in the insulated container and the changes in chemical and organoleptic qualities of different varieties of fish under condition of transport are also discussed.